2021
DOI: 10.3389/fpsyt.2021.741059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Behavioral and Psychological Symptoms of Dementia in Community-Dwelling Dementia Patients: A Systematic Review

Abstract: Background: Identifying the characteristics of behavioral and psychological symptoms of dementia (BPSD) associated with different dementia types may be a promising strategy to effectively deal with BPSD. We aimed to synthesize the prevalence rates of BPSD characteristics in community-dwelling dementia patients.Methods: We searched Medline, EMBASE, and PsycARTICLES databases for original clinical studies published until December 2020 that enrolled at least 300 community-dwelling dementia patients. The methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…For example, we did not control for whether participants had been diagnosed with depression before they were diagnosed with dementia. An important implication for future studies would be looking at clusters of the various types of dementia, as they manifest different behavioural and psychological symptoms [ 63 ], which may affect the subjective experiences and also perception of dignity in PwD. The relationships found might also have been influenced by the cultural context in which the study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we did not control for whether participants had been diagnosed with depression before they were diagnosed with dementia. An important implication for future studies would be looking at clusters of the various types of dementia, as they manifest different behavioural and psychological symptoms [ 63 ], which may affect the subjective experiences and also perception of dignity in PwD. The relationships found might also have been influenced by the cultural context in which the study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review, indicated that 82% of residents of nursing homes exhibited at least one neuropsychiatric symptoms, with agitation and apathy being most prevalent (10). The prevalence of specific behavioral and psychological symptoms of dementia (BPSD) was the focus of a recent systematic review, which reported rates of specific symptoms low prevalence (4% for elation and mania) to higher prevalence (32% for apathy) with varying symptoms identified depending on dementia sub-type (11). The authors reported that apathy, depression, anxiety, irritability, agitation and aggression were common individual BPSD symptoms in patients with Alzheimer's disease, and depression and agitation and aggression were common in patients with.…”
Section: Neuropsychiatric Symptoms and Psychoactive Prescribing In Nu...mentioning
confidence: 99%
“…The behavioral and psychological symptoms of dementia (BPSD), including agitation, aggression, apathy, wandering, depression, and sleep disturbance, that occur during the course of dementia render care at home, in nursing homes, and in hospital environments difficult and are major causes of care burden [ 6 ]. A recent systematic review indicated that the prevalence of BPSD in community-dwelling patients with dementia varied from 4% to 32% depending on the symptoms, among which include apathy, depression, anxiety, irritability, agitation, aggression, sleep disorders, and eating disorders [ 7 ]. BPSD is not usually caused by a single etiology, but rather it is triggered by patient factors, such as unmet needs, pain, comorbidities, and personality, and environmental factors including caregiving quality, life events, caregiver distress, and family dynamics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%